A plasmonic chip-based bio/chemical hybrid sensing system for the highly sensitive detection of C-reactive protein. Issue 20 (10th December 2015) - Matsuura, Ryo; Tawa, Keiko; Kitayama, Yukiya; Takeuchi, Toshifumi
Abstract : A synthetic polymer ligand-grafted plasmonic chip was fabricated and demonstrated a highly sensitive detection of C-reactive protein (CRP) by grating-coupled surface plasmon field-enhanced fluorescence. Abstract : A synthetic polymer ligand-grafted plasmonic chip was fabricated and demonstrated a highly sensitive detection of C-reactive protein (CRP) by grating-coupled surface plasmon field-enhanced fluorescence. Poly(2-methacryloyloxyethyl-phosphorylcholine) was used as a CRP-specific polymer ligand layer and was grafted onto the plasmonic chip using surface-initiated controlled/living radical polymerization (limit of detection: ca. 10 pM).